LH-21, a CB1 antagonist, reduces hepatotoxic damage produced by paracetamol overdose in a mice model. - Rodríguez-Pozo, Miguel; Gavito, Ana Luisa; Jagerovic, Nadine; Rodriguez-de-Fonseca, Fernando; Suárez-Pérez, Juan; Rivera-González, Patricia; Decara, Juan (My University, 2023)
Drug-induced liver injury (DILI) is one of the main causes of hepatic acute failure. Paracetamol can cause it when is ingested in excessive doses, leading to the depletion of the antioxidant mechanisms of the hepatocytes and a series of processes that conclude with cell death. One of the altered metabolic pathways is the endocannabinoid system (ECS), which has become a very interesting target to alleviate these events due to its involvement in inflammatory processes. For this reason, the triazole-derived compound LH-21, a cannabinoid receptor Cb1 antagonist, was used for the treatment of DILI in 8-week-old male C57BL/6 mice. In the present study, fasting mice were subjected to an oral overdose of paracetamol (300 mg/kg) and treated 2 hours later with 3 mg/kg of LH-21. After 24 hours, the animals were sacrificed and the livers were collected to determine the hepatic levels of metabolites related to antioxidant mechanisms, the expression of proteins involved in the generation of cellular damage and the transcription grade of the different components of the ECS. The observed results showed that LH-21 treatment raises GSH levels and total antioxidant capacity, in addition to reducing malondialdehyde values. Furthermore, the phosphorylation degree of Jnk and Stat3, as well as the activation status of Casp3, diminished. Regarding the ECS, the expression of Ppara, Cnr1, Cnr2 and Gpr55 did return to normal levels. This suggests that LH-21 effectively blocks the Cb1 activity, allowing the correct function of Ppar-α that promotes a cellular anti-inflammatory state and the relief of the symptoms produced by DILI. These results exhibit a promising perspective for the prevention or treatment of some toxic effects of paracetamol overdose with LH-21. Nevertheless, these findings are a first step to continue studying the involvement of the ECS in this type of liver disease and investigating the effectiveness of this Cb1 antagonist against the pathophysiology of DILI.
Keywords: Medicamentos - Abuso; Hígado - Lesiones y heridas; LH-21; Paracetamol; Endocannabinoid system; Cb1; Ppar-α